Water resource safety assessment and limiting factor diagnosis based on improved concept and matter–element analysis models: a case study of a typical karst area in southwest China - Tao Peng; Tao Peng; Lei Zhao; Peng Wang (Frontiers in Environmental Science)
Water is an important strategic resource for sustainable development and a basic element for ecological environment construction, especially in the karst areas of southwest China. Based on the concept model of drive, pressure, engineering water shortage, status, ecological foundation, and response (DPESFR), we built a comprehensive assessment indicator system based on the characteristics of karst water resources. The entropy-weighted right, CRITIC, and analytic hierarchy process methods were used to determine three types of basic weights, and the coordinated weights of all indicators were obtained by combining the thought method of game theory. The matter–element analysis model was then used to calculate the water resource safety situation of Guiyang from 2013 to 2022, and the limiting factors were explored using the limiting degree model. Finally, the autoregressive integrated moving average (ARIMA) model was used to predict water resource safety of Guiyang from 2023 to 2030. The results of these analyses were as follows: (1) the integral situation of the water resource safety in Guiyang showed an annual downward trend. The water resource safety was found to be grade IV from 2013 to 2017 and grade III from 2017 to 2022; from 2023 to 2030, the integral water resource safety grade is expected to continue decreasing, with the integral level expected to remain at grade III. (2) In six subsystems of the criterion layer, the key limiting factors affecting the water resource safety of Guiyang were the “state” subsystem, followed by the “response” and “drive” subsystems, with the indicators under different subsystems being different. (3) The most influential factors limiting the degree were concentrated in the “state” subsystem, followed by the “response” subsystem, indicating that both human activities and natural conditions significantly impact water resource safety in Guiyang. By identifying and analyzing the indicators affecting water resource safety in Guiyang, it is seen that measures such as controlling the total amount of industrial wastewater discharge, improving the treatment rates of domestic sewage, ensuring ecological water usage, and promoting water-saving technologies are important prerequisites for ensuring water resource safety in Guiyang.